Facing death : where culture, religion, and medicine meet - Spiro, Howard M. (Howard Marget), 1924-2012; Curnen, Mary G. McCrea; Wandel, Lee Palmer (Yale University Press, 1996)
This is an important manual for those professionally involved with the dying, as well as a treatment & consolation for private readers. It brings together medical and humanities experts, to reflect on medical, cultural and religious responses to death.